The Effect of the Total Financing Value and Business Turnover on the Smooth Return of Murabahah Financing in MSMES in PT. Bank Muamalat KCP Cirebon - Muhammad Syahrul Adim; Siti Rohana (Journal of Islamic Economics and Finance, 2026)
Financing activities in Islamic banking require proper management due to the risk of repayment default by customers. The amount of financing and business turnover are assumed to influence the ability of MSME customers to fulfill their payment obligations. This study aims to analyze the effect of financing amount and business turnover on the smooth repayment of murabahah financing among MSME customers at PT. Bank Muamalat KCP Cirebon during the 2013–2022 period. This research employs a quantitative method with a saturated sampling technique consisting of 71 data points, analyzed using logistic regression, Wald test, t-test, F-test, and coefficient of determination through IBM SPSS 23. The results indicate that, simultaneously, the financing amount and business turnover have a significant effect on the smooth repayment of murabahah financing.